Iban Pop Song: Identity, Unity, and Belonging - Patrose, Abell Musi; Chee, Bong; Nur Afiqah, Mohamad Sa’id; Noor Athirah, Zaini; Nur Fatin Liyana, Ghazali; Collin, Jerome (Secholian Publication PLT, 2022)
Popular music has been known to convey a sense of togetherness and affiliation among diverse populations in multiethnic and multicultural nations. Malaysia is a unique case where local mainstream popular music has expressed a collective sense of unity and belonging among its multiethnic citizens and communities. Although numerous studies have examined this phenomenon, very little research has been conducted about the role of local indigenous popular music in communicating a sense of connectedness and inclusion among Malaysians from diverse backgrounds. The study presented in this paper set out to examine this by focusing on the role that Iban pop songs played for that reason. Through a public perception survey, the study gathered the views of 82 respondents from the Southern, Central and Northern regions of Sarawak on the famous Iban pop song, Biar Bekikis Bulu Betis by Andrewson Ngalai in terms of how it helped create ideas about unity and belonging among Sarawakians. The findings revealed that the participants asserted that Biar Bekikis Bulu Betis instils pride because it is synonymous with various occasions. The results also showed that the Biar Bekikis Bulu Betis song made the Sarawakian proud of their origin. The study has implications for future research as it highlights the necessity of acknowledging that the popular musical genre of the indigenous community can bring people together and feel closer to their home country